The Influence of the Belgian Constitution on Ottoman Constitutional Law - Mehmet Akad (Annales de la Faculté de Droit d’Istanbul)
The Belgian Constitution of 1831 is one of the constitutions that set an example during the preparation process of Ottoman constitutional law. The most important reason for this was the spirit of the Belgian Constitution, which brought together the monarch, parliament, and executive branch. Despite being inspired by the Belgian Constitution, Ottoman constitutional law was significantly different. The main objective of this study is to identify the similarities and differences between the two documents and to understand the spirit of Ottoman constitutional law. Therefore, to clarify the differences between documents, a comparative method is adopted primarily centered on articles that organize the structure and authority of the monarch and legislative and executive bodies. The main differences can be observed in the relationship among these three bodies. When the necessary provisions are compared, Ottoman constitutional law lacks specific provisions that might allow the development of equitable harmony between the monarch, parliament, and cabinet. More precisely, Ottoman constitutional law did not have the foundations for limiting the sultan’s power and creating a balanced division of power among the three bodies. Consequently, despite their similarities, Ottoman constitutional law lacks certain elements that allow it to be called a constitution; therefore, it is instead referred to as a constitutional charter.